OPEN EDUCATION IN POST – GRADUATE STUDIES - Delgado Santa Gadea, Kenneth (2014)
Due to the globalization and the deregulation processes in higher education, and mainly in post graduate education, we have noticed a trend towards curriculum internationalization, as new graduates from any country are considering in getting job opportunities worldwide. This means searching for and applying new curriculum innovations using technology as an avenue for open education or distance learning to achieve what is called e-learning.